Analysis Of The Quality Of Islamic Religious Education Teaching Materials In Fostering An Attitude Of Tolerance Among Students At SMP 07 Muhammadiyah Medan - Syahril, Muhammad (Yayasan Rahmat Islamiyah, 2024)
This study aims to analyze the quality of Islamic Religious Education (PAI) teaching materials in fostering an attitude of tolerance among students at SMP 07 Muhammadiyah Medan. The research employed a qualitative approach, utilizing content analysis of the teaching materials and interviews with PAI teachers and students. The study found that the PAI materials in this school generally supported the cultivation of tolerance values, emphasizing understanding, respect, and acceptance of diversity. However, the content needed further refinement in addressing interfaith and intercultural tolerance. The findings suggest that PAI teaching materials play a significant role in promoting an inclusive attitude among students, but continuous improvement is needed to ensure that tolerance is integrated more comprehensively. The study highlights the importance of evaluating and enhancing teaching resources to align with the goals of fostering peace and mutual respect in a diverse society.